(untitled) (Literary Voice, 2024)
The long mendicant era of the Indian National Congress (1885-1905) created a need for a leader in Indian nationalist politics who could rally the populace to struggle for political independence from the British. Sri Aurobindo fulfilled that space and employed his ideas of nationalism that has been the subject of scholarly debate for a long period. His inclusive national strategies to stir the entire nation played a key role. But his conception of nationalism goes beyond the struggle for freedom. He was on a mission to create a new country based on India’s rich spiritual and cultural heritage and modern European sciences. As far as India’s diversity is concerned, the task seemed greater than anything else. His writings especially in his journal Bande Mataram created waves among the masses. He appealed to the then-fragmented population to ascribe to the identity of one nation. His nationalism aimed at the Indian Renaissance through both political freedom and spiritual regeneration. This study will highlight most of the salient features of his nationalism.